Interesting Place Recommender System for Tourists - Shu , See Yong; Wan Ishak, Wan Hussain (Multidisciplinary Applied Research and Innovation, 2021)
Travel is a combination of different aspects which are likely to be experienced by most people in their life. Nowadays, information related to all the travel aspects is usually available on the Internet and some travel websites will provide travel packages for users. People will usually seek help when planning a trip. However, existing travel websites do not have a suggestion facility that can suggest suitable places based on the users’ needs and requirements. Hence, users found it difficult to plan their vacation. This project is aimed at developing an interesting place recommender system for tourists based on their background. In this project, a website application known as the Interesting Place Recommender System for Tourists (M’ Tourism) was developed. It is a website application that generates a list of recommended places for users based on their background. In more detail, this recommender system will match the users’ background that are deposited in this system and suggest a suitable travel place for the users based on the similarity of the users’ information with the history of the other tourists. The development of this system is based on the waterfall model, which is a standard step-by-step approach to developing an application. The usability testing was conducted on 31 respondents by inviting them to use and test the system. The comments and feedback from the respondents were used to improve the system. The findings from the usability testing also reveal that M ’Tourism is an effective web application that allows users to search for the desired information. The respondents also agree that they feel more convenient in planning their vacation with the support from M’ Tourism.